The Effect of Difference Temperature on Cortisol, Glucose and Glycogen level of Uceng Fish (Nemacheilus fasciatus) - Wijaya, Harun; Widodo, Maheno Sri; Soeprijanto, Agoes (Graduate School, Universitas Brawijaya, 2019)
Nemacheilus is one of the genera of freshwater fish. The existence of Uceng fish (Nemacheilus fasciatus) in public waters is increasingly rare. Changes in water temperature in the maintenance medium will affect the physiological processes of fish. The purpose of this study was to analyze physiological responses (blood glucose levels, cortisol, and glycogen hormones) of Uceng Fish (N. fasciatus) which were incubated at different temperatures and find out the initial time of Uceng fish adaptation to its new environment. Total of 200 fish were collected from wild catches in the Lekso River, Blitar. Fish tissue collection was carried out to test the profile of glucose, cortisol, and glycogen. The research activities at this stage were carried out by raising the Uceng fish from nature to a cultivation container in an aquarium of size 50 x 30 x 30 cm that given the different temperatures (20°C, 24°C, 28°C and 32°C), and each aquarium is filled with 10 Uceng fish and will be kept for 14 days. ELISA method was used to quantify the parameter. The result of this study showed highest peak of cortisol levels and blood glucose levels was achieved in the treatment of 24°C on the 10th day and the lowest in the treatment temperature of 28°C on the 6th day. The highest glycogen peak was reached at 32°C on day 10 and the lowest peak was reached at 28°C on day 2. We conclude that temperature affects the physiological response (cortisol, blood glucose, and glycogen) of Uceng fish (N. fasciatus). High levels of cortisol and blood glucose indicate stressful fish. Keywords: Fish, Nemacheilus fasciatus, Physiological, Temperature, Uceng.